2007
DOI: 10.1038/sj.ijir.3901578
|View full text |Cite
|
Sign up to set email alerts
|

Lower urinary tract symptoms and erectile dysfunction; links for diagnosis, management and treatment

Abstract: Recent large-scale epidemiological studies have documented a strong association between lower urinary tract symptoms (LUTS) and erectile dysfunction (ED). This observation has two important scientific and clinical aspects: (i) to reveal the pathomechanism linking LUTS and ED and (ii) to consider this fact in the individual approach for diagnosis and management of these two disorders. The following hypotheses are under investigation to explain the relation between LUTS and ED: (i) an increased Rho-kinase activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 37 publications
(42 reference statements)
2
25
0
3
Order By: Relevance
“…Previous studies have documented a clear association between LUTS and ED [12][13][14][15] . As OAB symptoms such as urgency, frequency and nocturia belong to the LUTS complex, a connection between OAB and ED seems likely.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented a clear association between LUTS and ED [12][13][14][15] . As OAB symptoms such as urgency, frequency and nocturia belong to the LUTS complex, a connection between OAB and ED seems likely.…”
Section: Discussionmentioning
confidence: 99%
“…Tadalafi l treatment in men with BPH has improved symptoms in 56% of men, but no change in urine fl ow was noticed; further research in the role of 5-PDEI in MPPS is needed [ 40 , 45 ]. All three available 5-PDEIs have been evaluated in the treatment of LUTS, and although men with severe LUTS report improvement in symptoms, more data are needed to support the routine use of 5-PDEIs to manage men with LUTS [ 46 ]. 5-PDEIs may be more useful in ejaculatory dysfunction because they relax seminal vesicles in isolated strips experiments [ 47 ].…”
Section: -Phosphodiesterase Inhibitorsmentioning
confidence: 98%
“…As has been demonstrated for men presenting with lower urinary tract symptoms (LUTS) [8], contemporary studies have found a correlation between LUTS, pelvic organ prolapse, and female sexual dysfunction [9,10]. By nature of their presentation for genitourinary problems, it is often a cumbersome task to establish a baseline for a patient's sexual function that can later be compared with outcomes of incontinence or prolapse surgery.…”
Section: Introductionmentioning
confidence: 97%